Can shared leadership stimulate team members’ proactive behaviour? Exploring through the bridge of psychological empowerment - Jue Wang; Hae-Ryong Kim; Thi Bich Hanh Tran (Tourism & Management Studies)
With the aim of investigating shared leadership in conjunction with team members’ proactive behaviours, the main focus of this study is on the role of job crafting and knowledge sharing, as well as psychological empowerment as a potential mediator in the process. A survey research design was utilised in this study to gather data from 186 highly technical and knowledge-based members of different teams of South Korean firms. The results indicated that shared leadership is effective in a team context, positively affects members’ job crafting and knowledge sharing in a team context, and strongly promotes psychological empowerment. Furthermore, we found the intermediary effects of psychological empowerment. As one of the first to theoretically clarify, this study empirically tests and proves that shared leadership is a crucial antecedent for motivation and positive behaviours of team members. With the enlightening findings, the study offers valuable implications for leaders and managers to manage teams effectively.